Amino acid composition of processed fish silage using different raw materials - Vidotti, R. M.; Viegas, EMM; Carneiro, D. J. (Elsevier B.V., 2003)
The objective was to evaluate amino acid composition of silages produced from three raw materials. Commercial marine fish waste, commercial freshwater fish waste, and tilapia filleting residue were used to produce fish silage by acid digestion (20 ml/kg formic acid and 20 ml/kg sulfuric acid) and anaerobic fermentation (50 g/kg Lactobacillus plantarum, 150 g/kg sugar cane molasses). Protein content and amino acid composition were determined for raw materials and silage. Marine fish waste had higher crude protein content (776.7 g/kg) compared to freshwater fish waste (496.2 g/kg) and tilapia filleting residue (429.9 g/kg). All silages lacked up to three amino acids for each product according to FAO standards for essential amino acids. However, considering as the limiting factor only the amino acids below the 30% minimum requirement for fish in general, all products were satisfactory with respect to essential amino acids. Therefore, the results suggest that all products investigated are appropriate for use in balanced fish diets. (C) 2003 Elsevier B.V. B.V. All rights reserved.
Keywords: essential amino acids; fish silages; fermented silage; acid silage